ZOEAL MORPHOLOGY OF PACHYGRAPSUS-GRACILIS (SAUSSURE, 1858) (DECAPODA, GRAPSIDAE) REARED IN THE LABORATORY - Brossigarcia, A. L.; Rodrigues, M. D. (Int Science Services/balaban Publishers, 1993)
The larval development of Pachygrapsus gracilis was studied in the laboratory under conditions of 25-degrees-C temperature and 20, 24, 28, 32 and 34 parts per thousand salinity. The objective of the study was to characterize the plankton phase of life of this species.
Keywords: LARVAL DEVELOPMENT; DECAPOD